Transfer of learning theories through recreational activities - Ana Elizabeth Vargas Vera; Franklin Gregorio Macías Arroyo; María Angélica Jara Castro; Lissette Estefanía Arias Macías (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.